Balancing connectivity with function in silver(i) networks of pyridyltriazole (tzpa) ligands results in the formation of a metallogel. Issue 22 (27th May 2020) - Hegarty, Isabel N.; Dalton, Hannah L.; Lynes, Amy D.; Haffner, Benjamin; Möbius, Matthias E.; Hawes, Chris S.; Gunnlaugsson, Thorfinnur
Abstract : Triazolylpicolinamide (tzpa) ligands give a robust metallogel or a crystalline coordination network as a structural model on reaction with silver(i ). Abstract : A new flexible and divergent 1, 2, 3-triazol-4-yl-picolinamide (tzpa ) ligand 2 and the half-equivalent model ligand 1, both functionalised with pendant 3-pyridyl groups, are reported and their coordination behaviour with silver(i ) ions is explored, both in the crystalline phase and through the formation of a supramolecular metallogel. The self-assembly of tzpa ligand 1 with AgCF3 SO3 resulted in the formation of a 1D coordination polymer, binding in a bidentate fashion through the pyridyl and triazole nitrogen atoms of the tzpa binding site and a pendant pyridyl nitrogen atom of an adjacent ligand. Doubling the number of metal binding sites in ligand 2, while retaining the same metal binding domain, gives rise to the formation of a supramolecular metallogel on reaction with AgBF4 at 5 wt% in MeCN, possessing self-healing properties.